Maqashid Syariah on Hajj Insurance in Indonesia - Indrarini, Rachma; Ghozali, M. L.; Yasid, A. (Technium Social Sciences Journal, 2022)
The pilgrimage is a risky worship because the pilgrims perform the pilgrimage for one month, in a different place and climate. The Indonesian government has regulated policies related to BPIH (Cost for the Implementation of Hajj). Where in BPIH there is also an insurance component to protect pilgrims from risks. The protection provided is in the form of insurance facilities. This study aims to look at the maqashid sharia component of sharia insurance because basically everything that is done by a Muslim must aim at the benefit or welfare in the world and in the hereafter. This study used a descriptive qualitative approach where in-depth interviews were conducted with the research subjects. The results of this study are from the five maqashid sharia (religion, soul, mind, lineage and property) the participation of pilgrims will fulfill the four of maqashid namely religion, soul, lineage and property.